Availability evaluation of scalable complex networks - Al-Khateeb, Wajdi Fawzi Mohammed; Al-Khateeb, Khalid A. Saeed; Al-Irhayim, Sufyan (2012)
This paper presents an efficient technique for availability evaluation of scalable complex network. The proposed technique is based on a decomposition process of a complex n-tuple bridge network into 2n simple subnetworks, whose reliabilities are easily found through availability/unavailability product rules. The decomposition is realized through a simple “binary” mapping process, Binary Decomposition (BD). The merit of this technique is manifested through its scaling power compared with the traditional decomposition technique. The decomposition process is achieved through one single step mapping as compared to 2n-1 steps in the traditional one. Furthermore, the evaluation of the subnetworks reliabilities is simplified as the binary index serves as indicator for the individual subnetwork topology. Two formulas are developed for the availability evaluation of the n-tuple bridge complex network, one for arbitrary link availability and a second for identical link availability.